Ethnomathematics in Jogi dance: An exploration of geometric concepts in Batam Malay traditional arts - Fauziah Fauziah; Yesi Gusmania; Nailul Himmi (State Islamic University of North Sumatra, 2025)
This study explores ethnomathematical elements in Jogi Dance, a traditional Malay art from Batam, identifying opportunities for its use in contextual geometry education. Using qualitative ethnographic design, data were collected through systematic observation of seven main dance movements, in-depth interviews, visual documentation, and literature review. Analysis employed the Spradley model to map cultural structure and emerging mathematical concepts. Results revealed that Jogi Dance embodies concepts of angles, lines, triangles, circles, rotations, translations, reflections, number patterns, and periodic functions reflected in movements, floor patterns, and dancer formations. These findings open opportunities to develop various learning media, including contextual geometry worksheets based on dance movements, floor pattern diagram modules representing transformations, motion analysis videos, and digital modeling using GeoGebra. Integrating local culture through Jogi Dance helps students understand abstract mathematical concepts concretely while supporting cultural preservation and character formation aligned with the Pancasila Student Profile. Although exploratory-descriptive, the mapping of ethnomathematical concepts and potentials serves as a fundamental stage before developing learning models or effectiveness tests, providing a solid foundation for pedagogical innovations that educators and teachers can maximize.